Everyware : the dawning age of ubiquitous computing - Greenfield, Adam (Voices That Matter Ser., 2006)
Ubiquitous computing--almost imperceptible, but everywhere around us--is rapidly becoming a reality. How will it change us? how can we shape its emergence? Smart buildings, smart furniture, smart clothing ... even smart bathtubs. networked street signs and self-describing soda cans. Gestural interfaces like those seen in Minority Report . The RFID tags now embedded in everything from credit cards to the family pet. All of these are facets of the ubiquitous computing author Adam Greenfield calls "everyware." In a series of brief, thoughtful meditations, Greenfield explains how everyware is already reshaping our lives, transforming our understanding of the cities we live in, the communities we belong to--and the way we see ourselves. What are people saying about the book? "Adam Greenfield is intense, engaged, intelligent and caring. I pay attention to him. I counsel you to do the same."--HOWARD RHEINGOLD, AUTHOR, SMART MOBS: THE NEXT SOCIAL REVOLUTION "A gracefully written, fascinating, and deeply wise book on one of the most powerful ideas of the digital age--and the obstacles we must overcome before we can make ubiquitous computing a reality."--STEVE SILBERMAN, EDITOR, WIRED MAGAZINE "Adam is a visionary. he has true compassion and respect for ordinary users like me who are struggling to use and understand the new technology being thrust on us at overwhelming speed."--REBECCA MACKINNON, BERKMAN CENTER FOR INTERNET AND SOCIETY, HARVARD UNIVERSITY Everyware is an AIGA Design Press book, published under Peachpit's New Riders imprint in partnership with AIGA.